2017
DOI: 10.1155/2017/2814581
|View full text |Cite
|
Sign up to set email alerts
|

Control of Passion Fruit Fungal Diseases Using Essential Oils Extracted from Rosemary(Rosmarinus officinalis)and Eucalyptus(Eucalyptus agglomerata)in Egerton University Main Campus Njoro, Kenya

Abstract: Growth of fruits which form an important part of human diet has been jeopardized by the many fungal diseases that are present today. This study was conceived to isolate the most common fungal pathogens in passion fruits. Fungi were isolated using potato dextrose agar in addition to characterization using morphological, cultural, and biochemical means. Extraction of essential oils from rosemary (Rosmarinus officinalis) and eucalyptus (Eucalyptus agglomerata) was done. Before carrying the sensitivity test of ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…It has been shown that increasing heating time would increase the amount of essential oil extracted. For instance, heating for 20-70 min extracts 0.2-0.6%, whereas heating for 180 min acquires 1.4-4% of essential oils [10,11]. However, in the present study, the heating time was 180 min, but the amount yield was low than expected.…”
Section: Resultscontrasting
confidence: 68%
“…It has been shown that increasing heating time would increase the amount of essential oil extracted. For instance, heating for 20-70 min extracts 0.2-0.6%, whereas heating for 180 min acquires 1.4-4% of essential oils [10,11]. However, in the present study, the heating time was 180 min, but the amount yield was low than expected.…”
Section: Resultscontrasting
confidence: 68%
“…Amylase, protease, and cellulase activities were determined by starch agar, skim milk agar, and carboxymethylcellulose agar, respectively ( Waithaka et al, 2017 ; Khalil et al, 2021 ; Xu et al, 2022 ). Plant growth-promotion (PGP) tests include indole acetic acid (IAA) production, siderophores production, and phosphate solubilization ( Shcherbakova et al, 2018 ; Lotfi et al, 2022 ; Mirskaya et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…spp., Colletotrichum spp., P . spp., A. flavus , and A. niger ) in crops (Waithaka et al., 2017), the protection of cultural relics (Tomić et al., 2023), the treatment of urinary tract infections (Ortega‐Lozano et al., 2023), and dermatophytosis with promising development prospects (Mugnaini et al., 2013).…”
Section: Biological Activities Of Rosemary Extractmentioning
confidence: 99%